Effectiveness Implementation of Green Sukuk in Support Financial Sustainable Finance in Islamic Commercial Banks in Indonesia - Muhammad Nur Husen; Zakiyyah Ilma Ahmad; Abdul Wakhid (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
Development draft sustainable finance push institution Islamic finance for integrate principle sustainability in activity business and investment . One of the instruments that have potential big in support financing sustainable is green sukuk , namely sukuk whose results its publication allocated For projects friendly environment in accordance with sharia principles . Research This aim For analyze effectiveness implementation green sukuk in support implementation Sustainable finance in Islamic Commercial Banks in Indonesia. Research use approach quantitative with method explanatory . The data used is secondary data obtained​ from report Islamic General Bank finance , report sustainability report , publication​ Financial Services Authority (OJK), Bank Indonesia, and the Ministry of Finance of the Republic of Indonesia during 2020–2025 period . Data analysis was carried out use multiple linear regression For test influence implementation green sukuk to indicator finance proxied sustainability​ through growth financing green , profitability , quality assets , and Environmental, Social, and Governance (ESG) values . Research result show that implementation green sukuk influential positive and significant to improvement financing green , strengthening image bank sustainability , as well as improvement investor confidence . In addition , the implementation green sukuk participate increase efficiency fund management and encourage growth asset productive development - oriented​ low carbon . Although Thus , the effectiveness implementation green sukuk Still face various challenges , including limited​ project green that fills sharia criteria , low market literacy regarding instrument finance green sharia, as well as Not yet optimally harmonization regulations and standards reporting sustainability . Research This conclude that green sukuk is instrument effective Islamic finance in support implementation sustainable finance at Islamic Commercial Banks in Indonesia, so that required strengthening policy , innovation products , as well as collaboration between regulators, industry banking , and investors to expand its utilization in reach objective development sustainable.